Impacto de las políticas públicas en la prevención y atención de la violencia de género en la parroquia venus cantón quevedo, durante el periodo 2023-2024. - Herrera Tamayo, Mariuxi Elizabeth (2025)
This study explores how human rights, gender inequality, and dysfunctional homes are interconnected, showing how these factors perpetuate cycles of violence. Based on child-family theory, it analyzes how these dynamics impact child development and affect family structure. It was found that rigid gender roles and traditional social expectations exacerbate violence in problematic family contexts, highlighting the urgency of comprehensive public policies that promote more equitable gender relations and improve family well-being. The research focused on women over 18 years of age residing in the Venus del canton Quevedo parish, with a total population of 26.578 according to SENPLADES data. A representative sample of 372 women was selected. Through structured surveys, key data on the prevalence of gender-based violence and access to support services were collected. To ensure the reliability of the results, closed-ended questionnaires and Cronbach's alpha were used. This quantitative approach allowed us to evaluate the effectiveness of public policies and propose evidence-based strategies to build safer and more equitable family environments. The findings indicate that integrated actions are needed to address the identified gaps. These include strengthening communication to raise community awareness, increasing the budget for improving infrastructure and services, and providing continuous training to the personnel involved. Furthermore, it is essential to enhance inter-institutional coordination and promote prevention strategies that foster gender equity and strengthen family well-being. This approach will help reduce cycles of violence and ensure a safer and more dignified life for the women in this community.